Pristine and Reassembled Nanosheets of Layered Perovskite-like Titanates HLnTiO4 and H2Ln2Ti3O10 (Ln = La, Nd) as Photocatalysts for Hydrogen Evolution - Sergei A. Kurnosenko; Oleg I. Silyukov; Ivan A. Rodionov; Iana A. Minich; Irina A. Zvereva (Solids)
Layered Ruddlesden–Popper titanates HLnTiO4 and H2Ln2Ti3O10 (Ln = La, Nd) have been exfoliated into nanosheets in aqueous tetrabutylammonium hydroxide and systematically investigated as hydrogen evolution photocatalysts. The nanosheets were tested both in as-prepared pristine form and after reassembly by two methods (simple filtration and precipitation by hydrochloric acid). The nanosheet-based samples demonstrated by up to 88 times greater photocatalytic performance in comparison with the bulk precursors and, after modification with a Pt cocatalyst, provided apparent quantum efficiency of hydrogen generation up to 14.2% in 1 mol.% aqueous methanol and 3.15% in pure water. It was established that the form in which the nanosheets are used strongly affects the hydrogen production efficiency: the latter typically decreases when moving from the pristine nanosheets to filtered ones and then to those restacked by hydrochloric acid, which is determined by the difference in their physical–chemical characteristics being influenced by the reassembly approach.